EXPERIENCE OF IMPLEMENTATION OF THE ALTERNATING STEEL BLOWING TECHNOLOGY IN CASTING LADLES AT OAO «BMZ» - A. S. Zazyan; S. V. Terletsky; V. A. Shatilo (Литьë и металлургия)
It is shown that application of the alternating steel conducting technology in casting ladles at OAO “BMZ” has increased the degree of metal desulphurization by 5% as compared to the melting of standard technology.